Analisis Pemustaka terhadap Pengembangan Desain Interior di UPT Perpustakaan Universitas Negeri Padang - Viola Alvina Santika; Marlini Marlini (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to analyze library user views on the development of interior design at the UPT Library of Padang State University, especially after the move from the old building to the new building. This is where the head of the UPT UNP Library focuses on incorporating interior design elements that can influence reader comfort, including lighting, air circulation, visual appeal that attracts library users to engage in all activities in the library, and the optimization of digital learning facilities. To collect data thru direct observation of participants, interviews with student, and photographic documentation of various service areas. Data analysis conducted thematically to identify patterns regarding spatial zones, interior design elements, and user comfort factors. Research findings reveal that interior design development has a real impact on library users' experience, particularly in terms of reading area comfort, space arrangement, and the availability of digital facilities. Therefore, good interior design is proven to emphasize the efficiency of the learning process for user satisfaction and enhance the library's reputation as a modern information center.